Analysis of Creative Thinking Test Items in Problem-Based Learning Integrated with Ethnoscience - Nurul Hidayah; Wahyuni Arafani; Agil Al Idrus; Agus Abhi Purwoko; Muntari Muntari (Yayasan Siti Widhatul Faeha Salahudin Syawal, 2025)
The need for culturally responsive science learning highlights the importance of assessment instruments that can capture students’ creative thinking skills. This study aims to analyze the validity and alignment of creative-thinking test items developed within a Problem-Based Learning (PBL) framework integrated with ethnoscience. The research used a Research and Development (R&D) design based on the ADDIE model, covering analysis, design, development, implementation, and evaluation. Essay-type questions were constructed to measure four indicators of creative thinking: fluency, flexibility, originality, and elaboration. Content validity was assessed by material and assessment experts using Aiken’s V. In contrast, qualitative descriptive techniques were used to examine the suitability of the items with creative-thinking indicators and ethnoscience contexts. The results show that all test items achieved very high content validity, with Aiken’s V values ranging from 0.86 to 0.92. Each creative-thinking indicator was represented proportionally, and all items were judged relevant to local cultural practices, particularly the salt-making process in Pejot Village and keris-making traditions in Sakra Village, East Lombok. The study concludes that the developed instrument is valid and feasible for assessing creative thinking skills in PBL-based science learning integrated with ethnoscience. These findings suggest that culturally grounded assessment instruments can enhance science education by fostering deeper, more creative student engagement with scientific concepts.